THE INFLUENCE OF THE @SIAPDARLING TIKTOK ACCOUNT ON GO GREEN BEHAVIOUR - Ghazian H. P., Muhammad; Andrini, Susi (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
The use of social media is utilised as a tool to find out information. One of them is information about Go Green behaviour. The social media in question in this case is social media with the TikTok account @siapdarling promoting information about lifestyle aspects of Go Green Behaviour. Go Green or also known as the greening movement is a social movement that seeks to protect and manage the surrounding natural environment in anticipation of a global crisis that can threaten environmental damage. The aim of this research was to investigate the impact of the Tiktok @siapdarling account on promoting environmentally friendly behaviour. This study employed the Explanatory Quantitative approach, with a focus on establishing and explaining the relationship between variables to test a hypothesis. The Slovin formula was utilised to determine the sample size of one hundred respondents from the followers of @siapdarling on Tiktok, with a margin of error set at ten per cent. Data was gathered through online questionnaires using google forms and analysed using SPSS version twenty-nine. The findings revealed a significant influence of the @siapdarling Tiktok account on encouraging Go Green Behaviour among its followers, while external factors also played a role in shaping behaviour. In general, this research provides benefits as information, insight, knowledge about Go Green Behaviour on the @siapdarling TikTok account and its followers, as well as being useful for academics who are interested in developing this research from a different perspective.